Analisis dan Perancangan Sistem Informasi Manajemen Donasi, Kegiatan, dan Relawan bagi Komunitas Sosial di Kota Malang (Studi Kasus: Komunitas TurunTangan Malang) - Mochammad Rifqi Ramadhani; Himawat Aryadita; Satrio Agung Wicaksono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
TurunTangan Malang is a social community located in Malang City and it is part of Turun Tangan Indonesia. Currently, TurunTangan Malang is engaged in several fields, including education, culture, environment, and other fields that are adjusted from the existing problems in Malang. During did social activities, Turun Tangan Malang has several problems. Problems faced are the need of funds in conducting activities, limited human resources and not good enough in volunteer management. From the problems stated above, it is necessary to analyze and to design an application that can help Turun Tangan Malang search for donations, managing activities and volunteers. In this research, The analysis and design process are used Rational Unified Process (RUP) method. in RUP Method, developer and user are together define all needs sepecification to be on system and control all required resourches in determining the scope. The RUP method also systematically controls the changes that occur in the system. This research results are modeling of current business processes and proposals, user needs lists use case modeling, system design and system prototypes. Moreover, evaluation is did of tracebility and cognitive walkthrough to trace the scope of needs with implementation and prototype review to the user.